Diagnostic difficulties in tuberculosis hospital at the bacterial excretion absence - Gusarova, А. Yu.; Prosvetov, Yu. V.; Kovalenko, О. A. (Modern medical technology, 2019)
A clinical case of conducting a diagnostic searching a patient with suspected recurrence of pulmonary tuberculosis in the absence of bacterial excretion is presented in the article.